Clinical application of exhaled nitric oxide measurement in pediatric lung diseases - Manna Angelo; Caffarelli Carlo; Varini Margherita; Dascola Carlotta Povesi; Montella Silvia; Maglione Marco; Sperlì Francesco; Santamaria Francesca (BMC, 2012)
Summary Fractional exhaled nitric oxide (FeNO) is a non invasive method for assessing the inflammatory status of children with airway disease. Different ways to measure FeNO levels are currently available. The possibility of measuring FeNO levels in an office setting even in young children, and the commercial availability of portable devices, support the routine use of FeNO determination in the daily pediatric practice. Although many confounding factors may affect its measurement, FeNO is now widely used in the management of children with asthma, and seems to provide significantly higher diagnostic accuracy than lung function or bronchial challenge tests. The role of FeNO in airway infection (e.g. viral bronchiolitis and common acquired pneumonia), in bronchiectasis, or in cases with diffuse lung disease is less clear. This review focuses on the most recent advances and the current clinical applications of FeNO measurement in pediatric lung disease.